Mengukur Tingkat Literasi Digital Siswa Sekolah Menengah Atas (SMA) di Madiun - Ana Dhoud Daroin; Siti Marhamatul Auliya (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
The purpose of this study was to assess the digital literacy level of high school students in Madiun Regency. This study uses a qualitative approach with a survey method. The research subjects were 202 students in senior high schools spread across the city and district of Madiun. The measuring instrument used in this study is New Media Literacy to measure the level of digital literacy of students. The results of this study indicate that the average digital literacy skills of students are already high at 3.78. The assessment indicators are based on four aspects, namely functional consuming, critical consuming, functional presuming, and critical presuming. In conclusion, students' digital literacy skills in Madiun are high, there must be an effort to direct those digital literacy skills to positive behavior and things for adolescent development. The recommendation for further research is to develop a digital literacy intelligence research instrument specifically for adolescents, so that the research results are more valid. The research site also needs to be compared with the results in rural and urban areas for better research results. DOI: https://dx.doi.org/10.17977/UM014v15i12022p031